1969
DOI: 10.1103/physrevlett.22.853
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Absorption in Solid Alpha Oxygen

Abstract: The far-infrared absorption spectrum of crystalline alpha oxygen (a-0 2 ) has been measured in annealed samples up to 20 mm thick. The prominent feature of the spectrum is a temperature-dependent absorption near 27 cm" 1 which appears to be an antiferromagnetic resonance mode, the first such collective excitation to be observed in a molecular solid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The spin-flop transition at H c =6.9 T was observed from the high field magnetization measurement, 18) and the FIR spectroscopy measurements revealed that two antiferromagnetic magnon modes exist in far infrared region at 190GHz and 810GHz at zero magnetic field. [19][20][21] However, the field dependencies of these magnon modes could not be clearly obtained from the FIR spectroscopy measurement using the polycrystalline sample. From the high field/high frequency ESR measurement, we have succeeded in clarifying the AFMR modes of the α-oxygen in wide frequency and magnetic field region, owing to the high resolution of the ESR compared with that of the FIR spectroscopy measurements.…”
Section: 14)mentioning
confidence: 98%
“…The spin-flop transition at H c =6.9 T was observed from the high field magnetization measurement, 18) and the FIR spectroscopy measurements revealed that two antiferromagnetic magnon modes exist in far infrared region at 190GHz and 810GHz at zero magnetic field. [19][20][21] However, the field dependencies of these magnon modes could not be clearly obtained from the FIR spectroscopy measurement using the polycrystalline sample. From the high field/high frequency ESR measurement, we have succeeded in clarifying the AFMR modes of the α-oxygen in wide frequency and magnetic field region, owing to the high resolution of the ESR compared with that of the FIR spectroscopy measurements.…”
Section: 14)mentioning
confidence: 98%
“…Blocker et al 9 found an absorption line at 27 cm Ϫ1 in the far ir which they assigned to an antiferromagnetic resonance mode. Mathai and Allin 10 observed a low lying mode at 27 cm Ϫ1 ͑at 4 K͒ by Raman scattering and clearly pointed out an isotopic effect at libron modes and no isotopic effect at the mode at 27 cm Ϫ1 ; consequently they attributed it to a magnon mode.…”
Section: Introductionmentioning
confidence: 98%
“…The spectrum of elementary excitations in the a phase consists of (besides acoustic modes) two libron modes at 43 and 78 cm -1 [2] and two magnon ones at 6.4 and 27 cm -1 [1,4]. No magnon excitations were found in the p phase and there is one twofold degenerated libron mode at 50 cm" 1 [2].…”
mentioning
confidence: 99%
“…
This paper reports the results of the first measurements of the thermal conductivity of the a, )3, and y phases of solid oxygen over the temperature range of 1-52 K. A simple qualitative analysis was performed to explain the observed anomalies in thermal conductivity, which manifested themselves by a jump at the a-fi transition, the anomalously weak temperature dependence in the p phase, and an increase of the conductivity with temperature in the y phase.PACS numbers: 66.70.+f, 31.70.Ks, 75.20.Ck, Solid oxygen, a unique crystal combining properties of a molecular crystal and a magnet, has been a subject of intensive experimental and theoretical studies during the last two decades (see, for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and references therein). The following picture has emerged as a result of those studies.
…”
mentioning
confidence: 99%
See 1 more Smart Citation